Yellow Maize farmers knowledge and Implementation of Spodoptera Frugiperda Comprehensive Control Strategies and their Sources of Information in Some Villages of Sohag Governorate in The Arab Republic of Egypt - Nosier, Hala Shokry; Zayed, Mohamed El-Sayed; El-Sayed, Mohamed AbdelFattah (Journal of agricultural, environmental and veterinary sciences, 2023)
This research aimed to identify both the levels of respondent farmers knowledge and Implementation of comprehensive control strategies of Fall Armyworm, It aimed to determine the rate of contribution of some examined independent variables with statistically significant correlations of the amount of knowledge respondents have of such strategies to interpret the variance in other dependent variables. Finally, determining the relative importance of the sources of information for the farmers interviewed by the methods of integrated control of Fall Armyworm. This research was conducted in Sohag governorate on six villages, namely on a sample of 180 respondents, and this sample represented 15% of the total, the data necessary to achieve the research objectives were collected using a questionnaire form whose data were collected through the personal interview of the research sample individuals, several statistical methods were used. The most important results were as follows: - About 65.55% of the respondents have a low and medium degree of knowledge of the methods of integrated control of fall armyworm, while it was found that 71.22% of the respondents with a degree implementation of low and medium of This is techniques -Two independent variables only explained 15.4% of the total variance in the degree of knowledge of the respondents about the methods of integrated control of the Fall Armyworm insect, namely: the degree of exposure of the respondent to sources of information, and the age of the respondent. - Two independent variables only explained 8.1% of the total variance in the degree of respondents’ implementation of integrated control methods for Fall Armyworm, namely: the degree of education of the respondent, and the area cultivated with maize. - The most important sources from which the farmers surveyed obtained their information about the methods of integrated pest management in Neighbors, relatives, and agricultural guide.